Development trajectories of Finnish managers’ work ability over a 10-year follow-up period - Feldt, Taru; Hyvönen, Katriina; Mäkikangas, Anne; Kinnunen, Ulla; Kokko, Katja (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVES ': 'The study investigated the development trajectories of managers’ work ability over a 10-year period. In addition, baseline factors affecting the development course were sought from the managers’ background variables, work resources, and attitudes. Differences in retirement age in the detected trajectory groups were also examined. ' ' METHODS ': 'Questionnaire data were collected from Finnish managers (N=1033) in 1996, 1999, and 2006. In 1996, the mean age of the participants was 44 (range 20–65) years, and 28.5%, 35.5%, and 36% of the participants were in upper, middle, and lower management, respectively. ' ' RESULTS ': 'The analysis identified the following five trajectories over the follow-up period: (i) work ability consistently excellent (N=662), (ii) work ability good but declining (N=252), (iii) work ability declined from good to poor (N=54), (iv) work ability improved from moderate to good (N=46), and (v) work ability consistently poor (N=19). In the first group, the participants were more likely to be younger and to work in upper management, as compared with the other groups. They also gave their job control, organizational climate, and organizational commitment the highest rating. The mean retirement age was the highest (61.3 years) in the two most favorable work ability groups (1 and 2) and the lowest (55.4 years) in the group “work ability consistently poor.” ' ' CONCLUSIONS ': 'Aging managers and lower-level managers are at risk of having their work ability develop in an unfavorable direction. Therefore, more attention should be given to psychosocial work conditions in organizations in order to prevent poor work ability.
Keywords: Finland; follow-up; job control; manager; organizational climate; organizational commitment; trajectory analysis; work ability; work ability index; work involvement